القيم الأخلاقية وجودة البحث العلمي: تحليل للمفهوم والعلاقة - طير عبد الحق; الصادق عاشور; عقبة ريمي (University Of Eloued جامعة الوادي, 2023)
The study aims to highlight the role of commitment to ethical values in improving the quality of scientific research, by adjusting the concepts of: scientific research, ethics of scientific research and quality of scientific research, then explaining and stating the ethical values that must be adhered to in the field of scientific research, as well as displaying forms and forms of fraud. The scientific researcher should avoid and move away from it. After that, quality standards in scientific research were presented and analyzed, beginning with general standards and then specification and focusing on the quality of: research idea, research problem, scientific hypothesis, method and tools, quotation and documentation ... and trying to link them to principles And moral values to highlight the strength of influence and the degree of relationship. The analysis showed that the nature and degree of the relationship between commitment to ethical values and the quality of scientific research is direct and strong, and it is difficult to separate and differentiate between them, due to the overlap and intertwining between ethical values and quality standards.
Ethical values and the quality of scientific research: an analysis of the concept and relationship
مداخلة
Keywords: البحث العلمي; أخلاقيات البحث العلمي; الغش العلمي; جودة البحث العلمي; research; scientific research ethics; scientific fraud; The quality of scientific research.